2002
DOI: 10.1074/jbc.m110473200
|View full text |Cite
|
Sign up to set email alerts
|

Altered Amelogenin Self-assembly Based on Mutations Observed in Human X-linked Amelogenesis Imperfecta (AIH1)

Abstract: A hallmark of biological systems is a reliance on protein assemblies to perform complex functions. We have focused attention on mammalian enamel formation because it relies on a self-assembling protein complex to direct mineral habit. The principle protein of enamel is amelogenin, a 180-amino acid hydrophobic protein that self-assembles to form nanospheres. We have used independent technical methods, consisting of the yeast twohybrid (Y2H) assay and surface plasmon resonance (SPR), to demonstrate the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…Thr-21 and Pro-41) mutations within the A-domain of amelogenin are affected with defective enamel formation, a disease known as amelogenesis imperfecta (63,64). Previously, we used plasmon resonance spectroscopy, dynamic light scatter, and atomic force microscopy to show that recombinant amelogenin that phenocopies these single amino acid mutations from man also results in defective selfassembly for amelogenin (22,65). Based upon the present gene replacement studies with engineered amelogenin in mice, we predict that altered interactions between the ameloblasts and the mutated amelogenin in the matrix of humans affected with amelogenesis imperfecta contribute to the defective mineralization and materials properties observed in their enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Thr-21 and Pro-41) mutations within the A-domain of amelogenin are affected with defective enamel formation, a disease known as amelogenesis imperfecta (63,64). Previously, we used plasmon resonance spectroscopy, dynamic light scatter, and atomic force microscopy to show that recombinant amelogenin that phenocopies these single amino acid mutations from man also results in defective selfassembly for amelogenin (22,65). Based upon the present gene replacement studies with engineered amelogenin in mice, we predict that altered interactions between the ameloblasts and the mutated amelogenin in the matrix of humans affected with amelogenesis imperfecta contribute to the defective mineralization and materials properties observed in their enamel.…”
Section: Discussionmentioning
confidence: 99%
“…16 In the case of the porcine species, under low pH aqueous conditions the monomeric form of amelogenin exists in an extended, unfolded state. 9 It is suspected that intrinsic disorder contributes to the structure and function of these proteins in self-assembly 5,9,15,[17][18][19][20][21][22] and in cellmatrix, protein-matrix, and protein-mineral interactions. [5][6][7][8][9][23][24][25] The main challenge is to elucidate how intrinsic disorder affects the molecular behavior and configuration of this unusual series of proteins, and how amelogenin molecular behavior, in turn, affects biomineralization within the enamel matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Recent NMR studies of recombinant porcine amelogenin (rP172) indicated that there are three primary regions that are structurally distinct. 9 These are the highly conserved N-terminus (P2-W45) 26 or the proposed selfassembly ''A domain'' (P2-M42), [20][21][22] the partially condensed, charged C-terminal domain (D155-D173), 9,[20][21][22] and the extended Pro, Met, Gln-rich central domain (T58-P154) 9,16 that contains the polyproline Type II I70-P89 and P102-P145 sequence regions. 9 Both terminal domains exhibited evidence of residual secondary structure, 9 and these terminal regions may represent putative regions for folding during amelogenin-target interactions or self-assembly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These signals culminate to orchestrate expression of the amelogenin gene, the major organic component of the enamel matrix. Amelogenin plays a key role in regulating proper enamel mineralization and is believed to regulate its own replacement by the mineral phase to create a woven hierarchical architecture that accounts for the unique material properties of enamel (2)(3)(4)(5). Mutations to the human amelogenin gene have been linked to patients with the inherited enamel defect X-linked amelogenesis imperfecta (6).…”
mentioning
confidence: 99%